Assessment of the ability of MGO based binary binders for the substitution of Portland cement for mortars manufacturing. (25th July 2022) - Seco, A.; del Castillo, J.M.; Espuelas, S.; Marcelino, S.; Echeverría, A.M.
Highlights: MgO binary binders showed lower hydration and reactivity than PC. Binders fineness influenced mortars workability. MgO mortars achieved close densities, slightly lower than PC one. Both MgO mortars overcame PC flexural strength before 90 days. PC-8 mortar overcame PC compressive strength before 90 days. Abstract: This article evaluates the ability of a magnesia kiln dust (PC-8) and a commercial calcined MgO (MCB100), combined with ground granulated blastfurnace slag (GGBS), as constituents of binary M-S-H binders. Mortars and pastes were manufactured and their properties were compared to those of Portland Cement (PC). MgO-based mortars showed an increase in setting time and higher fresh consistency. At earlier ages MgO mortars showed lower mechanical properties. At 90 days both MgO-based mortars overcame the PC flexural strength and PC-8 + GGBS also overcame its compressive strength. X-Ray Diffraction and Thermogravimetry tests demonstrated the presence of M-S-H in the pastes.